2013
DOI: 10.1155/2013/926937
|View full text |Cite
|
Sign up to set email alerts
|

LPS-Induced Inflammation Potentiates the IL-1-Mediated Reduction of LH Secretion from the Anterior Pituitary Explants

Abstract: Acting at the level of the brain, interleukin- (IL-)1β is considered to be one of the most potent downregulators of reproduction processes during immune/inflammatory challenge. IL-1β suppresses gonadotropin-releasing hormone (GnRH) secretion from the hypothalamus resulting in the inhibition of the luteinizing hormone (LH) release from the anterior pituitary (AP). However, the presence of IL-1β receptors in the AP suggests the possible direct action of this cytokine on LH secretion. The study was designed to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 32 publications
2
39
0
Order By: Relevance
“…It was also found that IL-1β increased the adrenocorticotropic hormone, LH, GH and TSH secretion in primary cultures of rat pituitary cells, while IL-6 stimulated prolactin, GH, FSH and LH release from rat pituicytes culture (Tsagarakis et al, 1998). On the other hand, the study performed on the sheep pituitary explants showed that IL-1β suppressed LH secretion (Herman et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…It was also found that IL-1β increased the adrenocorticotropic hormone, LH, GH and TSH secretion in primary cultures of rat pituitary cells, while IL-6 stimulated prolactin, GH, FSH and LH release from rat pituicytes culture (Tsagarakis et al, 1998). On the other hand, the study performed on the sheep pituitary explants showed that IL-1β suppressed LH secretion (Herman et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…In in vitro study on the cells from ovine pituitary gland, Braden et al (1998) showed that IL-1β and IL-1α stimulated the release of LH. However, the results of our ex vivo study on the ovine pituitary explants showed that IL-1β rather down-regulated LH secretion from the pituitary gland (Herman et al, 2013b). This suggests that circulating proinflammatory cytokines, particularly IL-1β released during an inflammatory condition, may directly affect LH secretion from the anterior pituitary cells and this direct mechanism may accompany the processes occurring at the level of hypothalamus.…”
Section: Indirect Effect Of Lps On Gnrh/lh Secretionmentioning
confidence: 69%
“…14 Previous studies found that inflammatory cytokines may have a direct effect on the pituitary gland to decrease LH secretion, and a direct effect on secretion of testosterone from the Leydig cell (these two factors will reduce TT). 15,16 There is dysregulation hypothalamic pituitary adrenal axis due to increased glucocorticoid production among obese patients and subsequent hypoandrogenism in men. 17 Additional evidence that low TT which caused by androgen deprivation treatment in patients with prostate cancer may lead to increases the risk of MetS as seen in Basaria et al, study.…”
Section: Discussionmentioning
confidence: 99%